Genetic and biological characterisation of a novel South African Cydia pomonella granulovirus (CpGV-SA) isolate - Motsoeneng, Boitumelo Madika (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2016)
The codling moth, Cydia pomonella (L.) (Lepidoptera: Tortricidae), is the primary pest of pome fruit cultivated worldwide. The control of this insect pest has been dependent on the frequent use of broad-spectrum chemical pesticides, which has led to the development of resistance in pest populations and negative effects on human health and the environment. The Betabaculovirus of C. pomonella has successfully been applied as a biological control agent in integrated pest management (IPM) programmes for the suppression of pest populations worldwide. Previously, all Cydia pomonella granulovirus (CpGV) biopesticides were based on a Mexican isolate (CpGV-M) and although these products are highly efficient at controlling C. pomonella, resistance cases have been reported across Europe. The identification of novel CpGV isolates as additional or alternative control agents to manage resistance is therefore necessary. This study aimed to genetically and biologically characterise a novel South African C. pomonella granulovirus isolate and to test its virulence against neonate larvae. Based on the morphology of the occlusion bodies observed using transmission electron microscopy, granuloviruses were recovered from diseased and dead larvae collected from an orchard in South Africa where no virus applications had been made. DNA was extracted and the identification of the isolated granulovirus was achieved through the PCR amplification and sequencing of the lef-8, lef-9, granulin and egt genes. Submission of the gene sequences to BLAST revealed high percentage identities to sequences from various CpGV isolates, resulting in the naming of the isolate in this study as the South African Cydia pomonella granulovirus (CpGV-SA) isolate. Phylogenetic analysis based on the single nucleotide polymorphisms (SNPs) detected in the lef-8, lef-9 and granulin nucleotide sequences grouped the South African isolate with CpGV-E2 (genome type B) and CpGV-S (genome type E). The CpGV-SA isolate was further genetically characterised by restriction endonuclease analysis and complete sequencing of the genomic DNA. Differences were observed for the BamHI, EcoRI, PstI and XhoI profiles of CpGV-SA in comparison to the respective profiles generated for CpGV-M extracted from a biopesticide, Carpovirusine® (Arysta Lifescience, France). Several genetic variations between the complete genome sequence of CpGV-SA and the reference isolate, CpGV-M1, as well as a recent genome submission of CpGV-M, both representing genome type A were observed. The complete genome analysis confirmed that CpGV-SA is genetically different from the Mexican CpGV isolate, used in thedevelopment of most biopesticides. In silico restriction profiles of the genome sequence obtained for CpGV-SA and genome sequences of genetically different CpGV isolates originating from Mexico (M1 and M), England (E2), Canada (S) and Iran (I12 and I07), available on the NCBI's GenBank database confirmed that CpGV-SA is of mixed genotypes. Furthermore, the South African isolate shared the single common difference found in the pe38 gene of resistance overcoming isolates, which was the absence of an internal 24 nucleotide repeat present in CpGV-M1. In addition to the common difference, SNPs detected in the pe38 gene grouped the isolate with the CpGV-S isolate, suggesting that the CpGV-SA isolate is predominantly of genome type E. To determine the biological activity of CpGV-SA against neonate C. pomonella larvae, surface bioassays were conducted alongside CpGV-M (Carpovirusine®) bioassays. The LC50 and LC90 values for the South African isolate were 1.6 × 103 and 1.2 × 105 OBs/ml respectively. The LT50 was determined to be 135 hours. These values were similar to the values obtained for CpGV-M (Carpovirusine®). The results in this study suggest that a novel South African CpGV isolate of mixed genotypes, potentially able to overcome resistance in C. pomonella, with biological activity similar to CpGV-M (Carpovirusine®) and important for the control of C. pomonella was recovered. The CpGV-SA isolate could therefore potentially be developed into a biopesticide for use in resistance management strategies against C. pomonella populations in South Africa.
Keywords: Uncatalogued